Some kind of happiness - Legrand, Claire, 1986- (Simon & Schuster Books for Young Readers, 2016)
Finley Hart is sent to her grandparents' house for the summer, but her anxiety and overwhelmingly sad days continue until she escapes into her writings which soon turn mysteriously real and she realizes she must save this magical world in order to save herself.